IMPORTANT BIOCONTROL TRAITS OF MICROBIAL ANTAGONISTS OF LEAF ROT DISEASE OF COCONUT - Alka Gupta (International Coconut Community, 2003)
Leaf rot disease of coconut, which occurs superimposed on root (wilt) disease of coconut in about 65 % of the cases, is an important disease prevalent in Kerala State of India. Colletotrichum gloeosporioides and Exserohilum rostratum are the main fungal pathogens of the disease, which disfigure the leaves and reduce yield substantially. Several biocontrol agents have been identified which reduce the disease development by these fungal pathogens. Pseudomonas spp. exhibit a host of mechanisms, which act in concert to bring about biocontrol activity. Bacillus spp. work mainly through production of antibiotics and other non-volatile metabolites. Mycoparasitism was the main contributing factor for actinomycetes group.